The Impact of Motivation and Work Culture on Employee Performance at PT. Bank Sulselbar - Trisnasari, Juniarto Dwi; Razak, Muh Mashur; Hatta , Moh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to determine the effect of motivation and work culture on administrative services through employee performance at PT. Bank Sulselbar Main Branch Makassar. The research was conducted in Makassar City at PT. Bank Sulselbar Main Branch Makassar, lasting for one (1) month, from November to December 2024. The population of this study consisted of all employees of PT. Bank Sulselbar Main Branch Antang, totaling 180 people. The sample was taken using the Slovin formula, with a 95% confidence level and a 5% margin of error, so the research sample from 180 people at a 95% confidence level is 124 individuals, consisting of both contract and permanent employees. Data collection techniques were carried out through observation, questionnaires, and documentation, while data analysis used SPSS ver. 25. The research results show that an increase in organizational culture values is positively and significantly associated with an increase in employee performance. The new findings of this study are (1) the increase in cultural values is significantly associated with performance improvement at PT. Bank Sulselbar Main Branch Makassar. (2) The increase in motivation significantly contributes to performance improvement at PT. Bank Sulselbar Main Branch Makassar. (3) Culture has a significant effect on the administrative services received at PT. Bank Sulselbar Main Branch Makassar. (4) Motivation has a significant effect on the administrative services received at PT. Bank Sulselbar Main Branch Makassar.